Genes e variantes genéticas na regulação da eficiência alimentar de gado Nelore - Lima, Andressa Oliveira de (2019)
Feeding accounts for most of the costs in beef cattle production. To reduce it, as well as the environmental impact, greenhouse gas emission, and land occupation have been mandatory to improve the animal feed efficiency. Multifactorial, feed efficiency (FE) has been evaluated by different indexes and approaches. Among them, genomic studies from animals genetically divergent for FE pointed out candidate genes and pathways such as energy metabolism, inflammatory and oxidative stress. However, these studies did not take into account the continuous variation of the gene expression within the population. Thereby, from a previous differential approach carried out in divergent Nelore steers for FE, we selected six hepatic candidate genes (COL1A1, CTGF, CYP2B6, EGR1, PRUNE2, and the PRUNE2_isoform) based on their biological role on pathways related to feed efficiency. We carried out a realtime quantitative PCR (RT-qPCR) assay in 52 Nelore steers to evaluate the hepatic expression profile of the overmentioned genes and their association with FE related-traits such as average daily gain (ADG), body weight (BW), dry matter intake (DMI), feed conversion ratio (FCR), feed efficiency ratio (FE), Kleiber index (KI), metabolic body weight (MBW), residual feed intake (RFI), and relative growth rate (RGR). Based on a linear mixed model, we identified that the total expression of PRUNE2 has an unfavorable effect on feed efficiency related-traits, likely related to mitochondrial dysfunction. However, when taking only the PRUNE2_isoform, we observed a favorable effect on the evaluated trait. Still, to shed light on the genetic mechanisms affecting feed efficiency in Nelore, we applied a coexpression approach using muscle RNAseq data from 180 animals. Based on the weighted gene co-expression network analysis (WGCNA) software, we identified 391 potential biomarkers (hub genes) related to feed efficiency variation. These hub genes partook in protein synthesis, muscle growth, and immune response pathways. Among the hub genes, we highlighted CCDC80, FBLN5, SERPINF1, and OGN genes, which were associated to ADG, FCR, FE, KI, and RGR traits, and were related to glucose homeostasis, oxidative stress, and osteogenesis. Furthermore, we found 13 transcription factors among the hub genes described for bovine and six of them are putative regulators for the others hub genes identified in this study. Among them, the TCF4 may have a role in muscle growth metabolism and regulator of DE genes for divergent RFI in muscle previously identified by our research group. Finally, we identified potential regulatory regions and functional variants related to the potential biomarkers identified in this study.